Adsorption of Amino Acids and Glutamic Acid-Based Surfactants on Imogolite Clays - Bonini, Massimo (Langmuir : the ACS journal of surfaces and colloids, 2017)
Aluminum oxide surfaces are of utmost interest in different biotech applications, in particular for their use as adjuvants (i.e., booster of the immune response against infectious agents in vaccines production). In this framework, imogolite clays combine the chemical flexibility of an exposed alumina surface with 1D nanostructure. This work reports on the interaction between amino acids and imogolite, using turbidimetry, ζ-potential measurements, and Fourier transform infrared spectroscopy as main characterization tools. Amino acids with different side chain functional groups were investigated, showing that glutamic acid (Glu) has the strongest affinity for the imogolite surface. This was exploited to prepare a composite material made of a synthetic surfactant bearing a Glu polar head and a hydrophobic C12 alkyl tail, adsorbed onto the surface of imogolite. The adsorption of a model drug (rhodamine B isothiocyanate) by the hybrid was evaluated both in water and in physiological saline conditions. The findings of this paper suggest that the combination between the glutamate headgroup and imogolite represents a promising platform for the fabrication of hybrid nanostructures with tailored functionalities